Serologic profile of bovine alfaherpesvirus type E 1 (BOHV-1) and pestivirus A ( BVDV-1) in herds of a family farming of the São Paulo state - Curci, Vera Claudia Magalhaes; Costa, Ricardo Lopes Dias da; Alexandrino, Bruna; Borges, Lucimara Antonio; Romaldini, Adriana Hellmeister de Campos Nogueira; Moreli, Fernando Christiano Gabriel; Bozzi, Alexandre da Rocha; Samara, Samir Issa [UNESP] (Inst Zootecnia, 2021)
Serum samples from 719 dairy cattle of reproductive age, from 47 farms in a settlement in the municipality of Andradina, Sao Paulo, were analyzed for the presence of antibodies against the Nebraska strain of BoHV-1 and Singer type 1 of BVDV-1, using the virus neutralization technique (VN). Regarding BoHV-1, 72.0% of the samples analyzed (518/719) were positive, with a geometric mean of antibody titers of 318. For BVDV-1, 44.8% of the samples were reactive, only one farm had no reactive animals, and the majority of antibody titers found in the animals' sera were low. The results of this study revealed that BoHV-1 was present in all of the studied herds, with moderate titration in the majority of cases, with the presence of some high individual titers among the tested animals. Also, even with the reactivation or circulation of BoHV-1 in herds, the clinical disease was not observed, an epidemiological finding that also applied to BVDV-1. In view of the results obtained, the circulation of diseases in family farm herds in the studied region was evident, suggesting the need to study local risk factors and improve health education policies as a way to prevent or reduce the prevalence of these diseases.
Keywords: Cattle; Reproductive diseases; Health; rural settlement; Serology